Treatment planning for patients with acoustic neuroma - Fishman, Andrew J.; Rosiak, Oskar; Rivera, Arnaldo; Puricelli, Michael; Zivkovic, Nenad; Mierzwinski, Jozef; Markovic, Bojan; Milisavlevic, Natalija; Rola, Radosław; Szymanski, Marcin (Frontiers in Oncology, 2025)
IntroductionAcoustic neuroma (AN) is a benign tumor of the vestibulocochlear nerve, with increasing detection due to improved imaging. Treatment decisions are complex, requiring an individualized approach based on tumor size, location, growth rate, and patient-specific factors such as hearing and vestibular function.ResultsTreatment options include observation, microsurgery, and stereotactic radiosurgery. Hearing preservation is prioritized in select cases using middle cranial fossa or retrosigmoid approaches, while translabyrinthine surgery is preferred for larger tumors or disabling dizziness. Stereotactic radiosurgery offers a non-invasive alternative but has variable long-term hearing outcomes and potential tumor regrowth. Vestibular rehabilitation is essential post-treatment, particularly after surgical resection.DiscussionDecision-making depends on patient age, tumor progression, and symptom severity. Younger patients with small tumors may benefit from early intervention to preserve hearing, while older patients with severe imbalance achieve better quality-of-life outcomes with surgery. Stereotactic radiosurgery remains an option for patients unable to undergo surgery, though its long-term efficacy and side effects require careful consideration. A multidisciplinary approach is essential to optimize treatment outcomes.SummaryAN management must be tailored to individual patient profiles. This review integrates current literature and expert clinical experience to guide otolaryngologists, neurologists, and oncologists in treatment planning. Future research should refine treatment algorithms and improve functional outcomes.